2017
DOI: 10.1016/j.ast.2016.12.026
|View full text |Cite
|
Sign up to set email alerts
|

A fast multi-objective optimization design method for emergency libration point orbits transfer between the Sun–Earth and the Earth–Moon systems

Abstract: This paper considers the emergency trajectory design mission of libration point orbit transfer between the Sun-Earth system and the Earth-Moon system. In order to balance the two indexes of transfer time and fuel consumption, Halo orbits and theirinvariant manifolds in the circular restricted three body problem (CRTBP) are combined with low thrust in the bicircular restricted four body problem (BRFBP) to design the transfer trajectories. A fast multi-objective optimization methodbased on surrogate modelwhich i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…One way to handle this problem is to introduce the lag equation as described in Eq. (8). The function of the lag equation is similar to a first-order filter, that can filter the control input signal and make the trend in the actual control history smoother.…”
Section: Flight Trajectory Problem Without No-fly Zone Constraintmentioning
confidence: 99%
See 2 more Smart Citations
“…One way to handle this problem is to introduce the lag equation as described in Eq. (8). The function of the lag equation is similar to a first-order filter, that can filter the control input signal and make the trend in the actual control history smoother.…”
Section: Flight Trajectory Problem Without No-fly Zone Constraintmentioning
confidence: 99%
“…Generally, this type of problem aims to find the optimal state and control sequences so as to optimize the predefined performance index. Relative works on this topic can be found in various scientific and engineering applications such as agent/robot trajectory planning [3], [4], autonomous vehicle optimal path design [5], and spacecraft optimal control systems [6]- [8]. More precisely, in [2] the author proposed a time-optimal trajectory generation strategy for a multi-body car model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this type of problem, the different objectives have a trade-off relationship, so there is no single optimal solution but a set of optimal solutions called the Pareto-optimal solution or noninferior solution. Common optimization algorithms include the MOGA, NPGA, PAES, and NSGA-II, and on this basis, for the trajectory optimization problem, a variety of optimization models are derived to effectively improve the algorithm performance [26][27][28]. In this paper, from the perspective of the solution convergence and diversity, the MOPSO algorithm proposed by Coello et al [29], which has shown outstanding performance, is used.…”
Section: B Multi-objective Optimization Model Solution Based On Mopsomentioning
confidence: 99%
“…Weighted-sum method (WS) [85] Physical programming method (PP) [86] Fuzzy physical programming (FPP) [33] Interactive physical programming (IPP) [87] Interactive fuzzy physical programming (IFPP) [88] Goal programming (GP) [89] Fuzzy goal programming (FGP) [75] Fuzzy satisfactory goal programming (FSGP) [32] Adaptive surrogate model (ASM) [90] hard to find a solution that can optimize all the objectives, it is then interesting to find all the pareto-optimal solutions and create the pareto-optimal set.…”
Section: Multi-objective Transcription-based Techniquesmentioning
confidence: 99%